Clinical profiles of SS-ILD compared with SS-NILD in a Chinese population: a retrospective analysis of 735 patients - Ting Guo; Yaomei Long; Qinxue Shen; Wei Guo; Wang Duan; Xiaoli Ouyang; Hong Peng (Annals of Medicine)
Background Interstitial lung disease (ILD) is a serious complication in patients with Sjögren’s syndrome (SS). Most studies on primary SS (pSS) with ILD are limited in sample size, and studies on secondary SS (sSS) with ILD are rare. This study aimed to elucidate both primary and secondary SS-associated ILD (SS-ILD) based on a large cohort.Methods The medical records of hospitalized patients diagnosed with SS at the Second Xiangya Hospital of Central South University from January 2010 to May 2020 were retrospectively reviewed. Clinical manifestations, medical history, biological results and imaging data were collected.Results Of the 735 SS patients enrolled in this study, 563 (76.6%) were diagnosed with pSS, 172 (23.4%) were diagnosed with sSS. Additionally, 316 (43.0%) were diagnosed with SS-ILD. No significant difference was found between the pSS and sSS groups concerning the incidence of ILD (p = .718). Factors associated with SS-ILD were older age (p < .001), male sex (p = .032), female sex at menopause (p = .002), Raynaud’s phenomenon (p < .001), low levels of albumin (p = .010) and respiratory symptoms (p < .001). The SS-ILD group showed higher counts of platelets (p < .001). The three most frequent high-resolution CT (HRCT) findings of SS-ILD were irregular linear opacities (42.7%), grid shadows (30.7%) and pleural thickening (28.5%). NSIP (56.3%) was the most frequent HRCT pattern. Compared with pSS patients with ILD (pSS-ILD) patients, sSS patients with ILD (sSS-ILD) patients had a higher incidence of proteinuria (p < .001) and hypercreatinaemia (p = .013), a higher level of erythrocyte sedimentation rate (ESR) (p = .003), low levels of complement 3 (C3) (p = .013), lymphocytes (p = .009) and leukocytes (p = .024), and worse DLCO (%Pred) (p = .035).Conclusions ILD is a common pulmonary involvement in both pSS patients and sSS patients. Older age, male sex, female sex at menopause, Raynaud’s phenomenon, low albumin levels and respiratory symptoms are risk factors associated with SS-ILD. NSIP is important HRCT feature of SS-ILD. sSS-ILD patients showed worse laboratory results and pulmonary function.KEY MESSAGEOlder age, male sex, female sex at menopause, Raynaud’s phenomenon, low albumin levels and respiratory symptoms are risk factors associated with SS-ILD.SS-ILD patients show higher counts of platelets and less purpura.sSS-ILD patients have worse laboratory results and pulmonary function.